Revue européenne des éléments finis - Dhatt Gouri (American : Hermes, 1993)
A numerical procedure for reynolds stress transport equations í presented using a semi staggeered grid. the sýtem formed by the stress equations í sloved by point implicit method in order to preserve the so important couplings for numerical stability. The method is then applied for two different turbulencce models to the prediction of the turbulent flow due to a rotating disk. the mean flow prediction are in good agreement with the experimental data, while for the turbulent field some discrepancies remain
Keywords: Finite volumes; Turbulence model; Rotating flow; Numerical stability; Semistaggered grid